Influence of Work Gratitude and Social Support on Subjective Well-Being of Healthcare Workers in DKI Jakarta - Rezky Eka Wardana (SOCIETIES: Journal of Social Sciences and Humanities, 2026)
Abstract. This research investigates the contribution of work gratitude and social support to subjective well-being among healthcare workers and volunteers in the Jabodetabek region. Individuals working in healthcare and volunteer roles are frequently exposed to intensive workloads and psychological strain, which may influence how they perceive and evaluate their overall quality of life. Employing a quantitative correlational approach, data were obtained from 250 respondents using self-report questionnaires assessing subjective well-being, work gratitude, and perceived social support. The collected data were analyzed through descriptive statistical techniques and multiple regression analysis. The findings demonstrate that work gratitude and social support jointly exert a significant influence on subjective well-being (R² = 0.354, p < 0.001). Further regression analyses indicate that work gratitude positively and significantly predicts subjective well-being (β = 0.372, p < 0.001), while social support also shows a positive and significant predictive effect (β = 0.341, p < 0.001). Additional analyses reveal that the magnitude of these relationships varies according to gender, occupational category, and age group. Overall, the results underscore the relevance of both internal psychological resources and external social factors in fostering subjective well-being among healthcare workers and volunteers. These findings position work gratitude and social support as key determinants of subjective well-being within occupational settings. Keywords: work gratitude; social support; subjective well-being; healthcare workers; volunteers